Pengaruh Fraksi Volume pada Green Composite Serat Bambu dengan Matriks Sari Pati Kentang Terhadap Stabilitas Termal Melalui Uji TGA - Castafiore, Kimi Obelix; Kencanawati, Cok Istri Putri Kusuma; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract The strategy of employing effective thermal insulators can serve as a solution to reduce energy consumption in buildings by mitigating energy loss due to heat transfer. However, most thermal insulators currently in use are made from petrochemical materials, posing potential environmental risks. Thus, the utilization of environmentally friendly materials such as green composite bamboo fiber with potato starch matrix can offer an alternative solution. This research employs potato starch matrix and bamboo fiber as reinforcement. The compositions of potato starch and bamboo fiber utilize volume fractions of 5% bamboo fiber: 95% potato starch, 7.5% bamboo fiber: 92.5% potato starch, and 10% bamboo fiber: 90% potato starch. Thermal testing methods utilized in this study include Thermogravimetric Analysis (TGA) following ASTM D7582 and microscopic analysis. TGA test data shows that the lowest moisture value is in the 5% fiber variation with 12.02% while the highest moisture value is in the 10% fiber variation with 21.71%, the lowest volatile value is in the 10% fiber variation with 76.55% while the highest volatile value is in the 5% fiber variation with 88.25%. The results of thermal stability analysis show that the highest 5% and 10% weight reduction temperatures are in the 10% fiber variation while the lowest is in the 5% fiber variation. Based on the results of microphoto observations, it can be concluded that for the 5%, 7.5%, and 10% variations of bamboo fiber, the percentage of voids is not much different, but the 5% bamboo fiber volume fraction variation has more voids in the matrix, while the 10% bamboo fiber volume fraction variation has more voids on the sides of the fiber. In accordance with the results of thermal stability, the variation with more voids on the sides of the fiber shows better thermal stability than the variation with more voids in the matrix. Keywords: Green Composite, Potato Starch, Bamboo Fiber, Volume Fraction, Thermogravimetry Analysis (TGA), Microscopic Analysi